2020
DOI: 10.3390/ijms21207732
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Function and Evolution of Taste 1 Receptor Gene Family in the Carnivore Fish Gilthead Seabream (Sparus aurata)

Abstract: A plethora of molecular and functional studies in tetrapods has led to the discovery of multiple taste 1 receptor (T1R) genes encoding G-protein coupled receptors (GPCRs) responsible for sweet (T1R2 + T1R3) and umami (T1R1 + T1R3) taste. In fish, the T1R gene family repertoires greatly expanded because of several T1R2 gene duplications, and recent studies have shown T1R2 functional divergence from canonical mammalian sweet taste perceptions, putatively as an adaptive mechanism to develop distinct feeding strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 97 publications
(108 reference statements)
1
8
0
Order By: Relevance
“…The highest level of expression and abrupt rise of sa T1R2b expression following first exogenous feeding and its earlier appearance in oropharyngeal tissues as deduced by the whole mount in situ analyses, suggests that this paralog may be playing major roles related to feeding. In support of this hypothesis, sa T1R2b/R3 was the most responsive and sensitive heterodimer to L-amino acid stimulations in this species ( Angotzi et al., 2020 ). Paradoxically, the sa T1R3 gene encoding the shared subunit of receptors signaling both sugar (T1R2/T1R3) and protein (T1R1/T1R3) rich foods in mammals ( Roper, 1989 ; Hoon et al., 1999 ; Adler et al., 2000 ; Yarmolinsky et al., 2009 ), and responding to a wide spectrum of L-amino acids (T1R1/T1R3 and T1R2 n /T1R3) in fish ( Oike et al., 2007 ), was among the lowest expressed gene throughout the larval stages analyzed.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…The highest level of expression and abrupt rise of sa T1R2b expression following first exogenous feeding and its earlier appearance in oropharyngeal tissues as deduced by the whole mount in situ analyses, suggests that this paralog may be playing major roles related to feeding. In support of this hypothesis, sa T1R2b/R3 was the most responsive and sensitive heterodimer to L-amino acid stimulations in this species ( Angotzi et al., 2020 ). Paradoxically, the sa T1R3 gene encoding the shared subunit of receptors signaling both sugar (T1R2/T1R3) and protein (T1R1/T1R3) rich foods in mammals ( Roper, 1989 ; Hoon et al., 1999 ; Adler et al., 2000 ; Yarmolinsky et al., 2009 ), and responding to a wide spectrum of L-amino acids (T1R1/T1R3 and T1R2 n /T1R3) in fish ( Oike et al., 2007 ), was among the lowest expressed gene throughout the larval stages analyzed.…”
Section: Discussionmentioning
confidence: 55%
“…In a recent study, we reported the complete T1R gene repertoire of gilthead seabream, consisting of eight members including sa T1R1 , sa T1R3 and six sa T1R2 ( a-f ), and functionally characterized the in vitro responses of a subset of heterodimers, namely sa T1R1 / R3 , sa T1R2a / R3 and sa T1R2b / R3 , to L-amino acids and sweet ligands ( Angotzi et al., 2020 ). Here, we further explored the mRNA expression profiles of all sa T1R in both larval and adult tissues.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations